Coumarin-based turn-on fluorescence probes for highly selective detection of Pi in cell culture and Caenorhabditis elegans. (September 2015) - Wang, Huan; Guo, Lin E.; Li, Xue Mei; Zhang, Li Mei; Xu, Qiu Lin; Wu, Gao Fen; Zhou, Ying; Zhang, Jun Feng
Abstract: Two coumarin-based fluorescence probes, 1 and2, containing a methoxy oxalyl group as a reaction site were developed. These two novel probes displayed an instant turn-on fluorescence response specific towards Pi without interference from ATP and PPi. A selective 23-fold increase in fluorescence for1 (in DMSO–HEPES) and a 20-fold increase for2 (in DMSO) were observed. The proposed sensing mechanism for these compounds is Pi-triggered acetamide bond cleavage leading to release of the blue fluorophore coumarin, which was supported by 1 H NMR and mass spectrometry data. Probe1 was successfully used to image endogenous and exogenous Pi in living cells and to trace Pi released from ATP by apyrase in Caenorhabditis elegans . Graphical abstract: A coumarin-based fluorescence probe1 displayed selective turn-on fluorescence with Pi and was successfully used to image endogenous and exogenous Pi in living cells and to trace Pi released from ATP by apyrase in Caenorhabditis elegans . Highlights: Two coumarin-based fluorescence probes containing a methoxy oxalyl group were developed. These probes displayed an instant turn-on fluorescence response specific towards Pi. The proposed sensing mechanism was supported by NMR and mass spectrometry data. Probe1 was successfully used to image endogenous and exogenous Pi in living cells. Probe1 could trace Pi released from ATP by apyrase in Caenorhabditis elegans .